The crack quasi-static growth and analysis of interlaminar crack resistance of layered composite - Pavelko Igor (EDP Sciences, 2021)
Using the model of quasi-static crack growth and test result of the double cantilever beam (DCB) sample of layred carbon/epoxy composite, the general regularities of the interlaminar crack resistance of mode 1 were studied. The main attention was focused on the variability of crack resistance associated, on the one hand, with the continuity of the fracture process, and, on the other hand, with the non-homogeneity of the material structure, which causes local random deviations from the average characteristics of the material.The dissipation energy rate (total crack resistance) and crack resistance function (R-curve) were extracted from test results and their properties analyzed.